2004
DOI: 10.1016/s0002-9440(10)63381-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of CCR4 Ligands, CCL17 and CCL22, During Schistosoma mansoni Egg-Induced Pulmonary Granuloma Formation in Mice

Abstract: Controversy persists pertaining to the role of CCR4 ligands, namely CCL17 (or thymus and activation regulated chemokine; TARC) and CCL22 (or macrophagederived chemokine; MDC), in Th2-type cytokine-dominated responses in the lung. Accordingly, the present study addressed the relative role of each of these CC chemokines during an evolving pulmonary granulomatous response elicited by the intrapulmonary embolization of live Schistosoma mansoni eggs into S. mansoni-sensitized mice. CCL22 protein expression peaked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 73 publications
3
62
0
Order By: Relevance
“…It also promoted liver regeneration in partially hepatectomized mice, which was shown in highly significant increases in weight, RNA content, and many hepatic proteins. The modulation of host immune response against SEA by L-carnosine could be comparable to the immune modulation of S. mansoni egg recorded by immunomodulators [42,43].…”
Section: Resultssupporting
confidence: 64%
“…It also promoted liver regeneration in partially hepatectomized mice, which was shown in highly significant increases in weight, RNA content, and many hepatic proteins. The modulation of host immune response against SEA by L-carnosine could be comparable to the immune modulation of S. mansoni egg recorded by immunomodulators [42,43].…”
Section: Resultssupporting
confidence: 64%
“…mansoni egg-induced granulomas require the efficient and sequential recruitment of a series of immune effecter cells, including macrophages, 36 CD4 ϩ T cells, 37 and eosinophils. 38 These specific immune cells form a strong cellular barrier and sequester the S. mansoni eggs from the surrounding healthy tissue. We and others have shown that the cytokine/chemokine network plays a central role in the recruitment and activation of immune cells around the eggs.…”
Section: Discussionmentioning
confidence: 99%
“…+ lymphocytes with a Th2 phenotype and CD25 + regulatory T cells (55)(56)(57)(58)(59), but also by natural killer cells, dendritic cells and macrophages (60). CCR4 is supposed to be important for regulating immune balance (61).…”
Section: Discussionmentioning
confidence: 99%